Entanglement classification for a three-qubit system using special unitary groups, SU(2) and SU(4) - Mohd S.M.; Idrus B.; Zainuddin H.; Mukhtar M. (Science and Information Organization, 2024)
Indexed by WOS/SCOPUS/ERA